Fairness properties of compensation schemes [dataset] - Becker, Christoph; Fehr, Dietmar; Rau, Hannes; Trautmann, Stefan T.; Xu, Yilong (Universität, 2026)
How do different characteristics of pay-for-performance schemes affect fairness perceptions? In two studies, we systematically consider three major classes of incentive schemes: continuous piece rate incentives, discrete bonus schemes, and tournament incentives. We find that pay inequality has a strong negative effect on perceived fairness. Controlling for pay inequality, people consider piece rate schemes fairer than those with a discrete bonus and a tournament design in particular. Adding performance-dependent resource advantages or handicaps negatively influences perceived fairness. We find that procedural fairness judgments are an important factor influencing overall judgments and demonstrate in a third study that the latter have relevant behavioral consequences.
Gesehen am 12.02.2026
Keywords: Forschungsdaten; Datenbank